2016
DOI: 10.3390/su8090799
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Environmental Load of Household Consumption Depend on Residential Location?

Abstract: Spatial planning aims to improve the socioeconomic and environmental sustainability of a region, yet, in the spatial planning framework, it is difficult to capture the environmental impacts of the lifestyle of residents as a whole. We use carbon load as an indicator for environmental pressure and explore the spatial variations in carbon load from transport, domestic energy use, and the consumption of goods based on data obtained from the Household Budget Survey in Estonia, in an attempt to understand how resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 90 publications
1
18
0
Order By: Relevance
“…Several recent studies highlight that further research on the underlying factors for consumption and lifestyle choices are important in order to understand how behavior and associated carbon footprints can be influenced. This includes understanding and modeling the choices of where people live in the first place (Gill and Moeller 2018), how they travel and migrate , how they interact within social, cultural and built environment networks (Poom and Ahas 2016), and how a sharing economy with environmentally beneficial outcomes could be supported , Fremstad et al 2018. Case studies specific to local circumstances and practices are as important as conceptual and generic models (Wiedmann 2016).…”
Section: Directions Of Future Researchmentioning
confidence: 99%
“…Several recent studies highlight that further research on the underlying factors for consumption and lifestyle choices are important in order to understand how behavior and associated carbon footprints can be influenced. This includes understanding and modeling the choices of where people live in the first place (Gill and Moeller 2018), how they travel and migrate , how they interact within social, cultural and built environment networks (Poom and Ahas 2016), and how a sharing economy with environmentally beneficial outcomes could be supported , Fremstad et al 2018. Case studies specific to local circumstances and practices are as important as conceptual and generic models (Wiedmann 2016).…”
Section: Directions Of Future Researchmentioning
confidence: 99%
“…The results from Europe vary, but the majority of the studies have found a small decreasing impact for an increasing degree of urbanisation, for example in the UK (Minx et al 2013), Finland (Ala-Mantila et al 2014), Sweden (Nässén et al 2015) and Germany (Gill and Moeller 2018). Some studies from Finland and Estonia highlight that the impact is largely statistically insignificant (Ottelin et al 2015, Poom and Ahas 2016, Ottelin et al 2018b. Similarly, Ivanova and colleagues found in their study of 27 EU countries that the impact of the degree of urbanisation on the carbon footprint is insignificant in the EU overall (Ivanova et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas are associated with high population and employment densities, compact and mixed land uses, and high degrees of connectivity and accessibility [20][21][22]; as such they have higher potential for collaborative consumption and sharing of resources between households, and more efficient uses of infrastructure [5], the so-called "compact" or "density effect" hypothesis [16]. This is because urban areas with narrower streets and smaller city blocks, compact and connected design, pleasant and safe urban space and mixed land uses generally reduce travel distance and promote active travel (walking and biking) and public transport [5,20,22]. Furthermore, urban dwellings are associated with smaller sizes, a higher proportion of apartments and multi-family houses and the presence of district heating, which are overall less carbon and energy intense per unit of area [3,22].…”
Section: Interaction Between Household Size and Population Densitymentioning
confidence: 99%
“…This is because urban areas with narrower streets and smaller city blocks, compact and connected design, pleasant and safe urban space and mixed land uses generally reduce travel distance and promote active travel (walking and biking) and public transport [5,20,22]. Furthermore, urban dwellings are associated with smaller sizes, a higher proportion of apartments and multi-family houses and the presence of district heating, which are overall less carbon and energy intense per unit of area [3,22]. While there is strong evidence for this density effect on per capita carbon and energy footprints in the European context, this is largely compensated by higher income levels in cities [23].…”
Section: Interaction Between Household Size and Population Densitymentioning
confidence: 99%